Difficult Paragonimiasis diagnosis in first level centers. Case report - Villacís, Sandra; Mena, Sixto; Acosta, Josué; Mora-Brito, Edgar; Leiva, Lizette; Carrero, Yenddy (Kasmera, 2020)
Patient who reports intake of crab without cooking presented a picture characterized by burning throat, respiratory distress and diarrheal depositions. Then cough and hemoptysis; went to a primary care center where they performed complementary exams establishing treatment without improvement, is referred to a hospital where Pulmonary Paragonimiasis was diagnosed.